Ammonia as a storage solution for future decarbonized energy systems - Aliaksei Patonia; Rahmatallah Poudineh (The Oxford Institute for Energy Studies, 2020)
This paper analyses whether ammonia can be viewed as an economically efficient and technologically suitable solution that can address the challenge of large-scale, long-duration, transportable energy storage in the decarbonized energy systems of the future. It compares all types of currently available energy storage techniques and shows that ammonia and hydrogen are the two most promising solutions that, apart from serving the objective of long-term storage in a low-carbon economy, could also be generated through a carbon-free process. The paper argues that ammonia, as an energy vector of hydrogen, is preferable to pure hydrogen from economic, environmental, and technological perspectives. It then analyses the available ammonia generation techniques, identifying conditions under which zero-carbon ammonia makes sense economically, and briefly highlights policy prerequisites for such production to be attractive for investors. Given the current state of the industry, large-scale deployment of green ammonia is unlikely to happen without policy supports such as adequate carbon taxes and/or alternative incentives. In the absence of such policies, green ammonia is only likely to make small-scale advances in the energy system, in areas with extremely low-cost renewable energy production or a significant surplus of generated energy.
Keywords: 330; ammonia; EL 42; electrolysis; green ammonia; green hydrogen; Haber Bosch process; Hydrogen; large scale storage; net-zero-carbon; steam reforming